Investigations into Salmonella Contamination in Feed Mills Producing Rations for the Broiler Industry in Great Britain - Rebecca Gosling; Claire Oastler; Christopher Nichols; George Jackson; Andrew D. Wales; Robert H. Davies (Veterinary Sciences, 2022)
Feed-associated Salmonella serovars continue to be reported in poultry flocks. A study was conducted to investigate Salmonella contamination in major commercial feed mills that produce rations for broiler chickens within Great Britain. Dust and large moist gauze swab samples (12,791) were collected from 22 feed mills on 31 visits. Salmonella was isolated from 20 mills, with 15 mills (75%) having fewer than 5% Salmonella-positive samples. Fifty-one Salmonella serovars were isolated, with a large proportion of isolates being Salmonella (S.) Kedougou (29.4%) or S. 13,23:i:- (21.4%). European Union-regulated Salmonella serovars (Enteritidis, Infantis, Typhimurium and its monophasic variants) were isolated from 12 mills, mostly from non-processing areas, accounting for 40 isolates (4.4% of all Salmonella-positive samples). Fifteen Salmonella serovars were only isolated once. In terms of individual sampling locations within the mill, the waste handling locations were significantly more likely to be Salmonella-positive than some other mill locations. When sampling locations were grouped, samples collected from finished product areas were significantly less likely to be Salmonella-positive for Salmonella than some other mill areas. In conclusion, this study found that most mills producing broiler rations showed low-level Salmonella contamination.